2014
DOI: 10.3389/fpsyg.2014.01305
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in associative learning: a cognitive stage framework for blocking and cue competition phenomena

Abstract: Blocking is the most important phenomenon in the history of associative learning theory: for over 40 years, blocking has inspired a whole generation of learning models. Blocking is part of a family of effects that are typically termed “cue competition” effects. Common amongst all cue competition effects is that a cue-outcome relation is poorly learned or poorly expressed because the cue is trained in the presence of an alternative predictor or cause of the outcome. We provide an overview of the cognitive proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 130 publications
(197 reference statements)
1
13
0
1
Order By: Relevance
“…This absence of US identity memory, in turn, is interpreted as an absence of S-S linkage. This demonstration is problematic because, in addition to the learning or encoding stage, one also has to consider the memory maintenance or retention, and retrieval or performance stages (e.g., Boddez, Haesen, Baeyens, & Beckers, 2014). Instead of being due to S-R learning, findings may be consistent with explicit encoding of (propositions about) CS-US co-occurrences if we consider what is known about memory maintenance: Forgetting occurs at a higher rate for more detailed, low-level (verbatim) information about a stimulus, whereas more abstract high-level (gist) information is retained over a longer time (e.g., Brainerd & Reyna, 2002).…”
Section: P2: S-r Linkagementioning
confidence: 99%
“…This absence of US identity memory, in turn, is interpreted as an absence of S-S linkage. This demonstration is problematic because, in addition to the learning or encoding stage, one also has to consider the memory maintenance or retention, and retrieval or performance stages (e.g., Boddez, Haesen, Baeyens, & Beckers, 2014). Instead of being due to S-R learning, findings may be consistent with explicit encoding of (propositions about) CS-US co-occurrences if we consider what is known about memory maintenance: Forgetting occurs at a higher rate for more detailed, low-level (verbatim) information about a stimulus, whereas more abstract high-level (gist) information is retained over a longer time (e.g., Brainerd & Reyna, 2002).…”
Section: P2: S-r Linkagementioning
confidence: 99%
“…The present account is located at a cognitive or algorithmic level of analysis (De Houwer & Moors, 2014;Marr, 1982). In discussing the present view and its basic hypotheses, it is necessary to distinguish between the cognitive processing stages of encoding or learning, main-Social Psychological Bulletin | 2569-653X https://doi.org/10.5964/spb.v13i3.28589 tenance or retention, and retrieval or performance (Boddez, Haesen, Baeyens, & Beckers, 2014). Contrasting dual-process accounts that focus on the learning stage, the present view holds that many of the dissociations reported in the literature involve later processing stages.…”
Section: Basic Hypothesesmentioning
confidence: 99%
“…However, as we have been advancing, the availability of more than one potential cause can result in a competition between both causes, so that if one is considered to be a strong candidate, the other will be seen as a weak one. Indeed, many experiments with both humans and other animals have reported that when two causes are presented together and followed by an outcome, one of the causes having a previous history of association with that outcome can compete with the attribution of causal strength to the most recent cause ( Shanks and Dickinson, 1987 ; Shanks, 2007 ; Wheeler and Miller, 2008 ; Boddez et al, 2014 ).…”
Section: When There Are Several Potential Causesmentioning
confidence: 99%